2005
DOI: 10.1007/s10569-004-3115-4
|View full text |Cite
|
Sign up to set email alerts
|

Report of the IAU/IAG Working Group on Cartographic Coordinates and Rotational Elements: 2003

Abstract: Every three years the IAU/IAG Working Group on Cartographic Coordinates and Rotational Elements revises tables giving the directions of the north poles of rotation and the prime meridians of the planets, satellites, and asteroids. This report introduces a system of cartographic coordinates for asteroids and comets. A topographic reference surface for Mars is recommended. Tables for the rotational elements of the planets and satellites and size and shape of the planets and satellites are not included, since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…A) The problem of the geodetic (relativistic) rotation of the Solar system bodies (the Moon, major planets, Pluto and the Sun) is studied with respect to the proper coordinate systems of the bodies (Seidelmann et al, 2005).…”
Section: Methods Of the Problem Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…A) The problem of the geodetic (relativistic) rotation of the Solar system bodies (the Moon, major planets, Pluto and the Sun) is studied with respect to the proper coordinate systems of the bodies (Seidelmann et al, 2005).…”
Section: Methods Of the Problem Solutionmentioning
confidence: 99%
“…The reduction of the components of the angular velocity vector of the geodetic rotation of the Solar system bodies, from the geocentric reference frame (the reference frame of DE422/LE422 ephemeris (Folkner, 2011)) to the body-centric reference frames, given by Seidelmann et al (2005), are found from the triangle (presented in Figure 1), which is used to define the direction of the angular velocity vector of the geodetic rotation for any body of the Solar system, by means of the following formulae: …”
Section: Methods Of the Problem Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of the geodetic (relativistic) rotation of the major planets, the Moon and the Sun was studied in the paper by Eroshkin and Pashkevich (2007) only for the components of the angular velocity vectors of the geodetic rotation, which are orthogonal to the plane of the fixed ecliptic J2000. This research represents an extension of the previous investigation to all the other components of the angular velocity vector of the geodetic rotation, with respect to the body-centric reference frame from Seidelmann et al (2005). …”
mentioning
confidence: 93%
“…Figure 1 depicts the triangle, which is used to define the components of the angular velocity vector of the geodetic rotation for any body of the Solar system. The reduction of the components of the angular velocity vector of the geodetic rotation of the solar system bodies, from the standard Earth equator J2000 (the reference frame of DE404/LE404 ephemeris) to the body-centric reference frames, given by Seidelmann et al (2005), is presented by the following expressions:…”
Section: Introductionmentioning
confidence: 99%